Kinetic features of ethanol steam reforming and decomposition using a biochar-supported Ni catalyst - Afolabi, Ahmed Tijani F.; Kechagiopoulos, P.N.; Liu, Yurong; Li, Chun-Zhu (2021)
The catalytic steam reforming of bio-ethanol will provide a sustainable route for renewable hydrogen production in a future hydrogen economy. Ni catalysts will be an economically attractive alternative to noble metals. Biochar is a promising reforming catalyst or catalyst support, having shown already good activity for tar reforming. The structure of biochar, its inherent alkali and alkaline earth metallic species and the content of O-containing functional groups are factors affecting its catalytic performance. A kinetic study of ethanol steam reforming and decomposition over a biochar-supported Ni catalyst is presented in this study in order to elucidate the role of biochar in the reaction mechanism. The effects of temperature, space velocity and reactant partial pressure were investigated over a range of conditions. The chemical structural features of used biochar samples were characterized with Raman spectroscopy. Biochar itself was found to be catalytically active and participating in ethanol reforming and decomposition. It was established that the reactions on Ni and biochar active sites were not independent. Analysis of kinetic compensation effects showed commonality on biochar and suggested that the rate-limiting step occurs in the dehydrogenation pathway on the biochar surface. O-containing functional groups in biochar were observed to reduce with reforming/decomposition time.